It's the end of the world... as we know it. The last capitalist pandemic? - Féliz, Mariano (2020)
The world is undergoing what will probably be a trascendental change. Capitalism has been getting deeper into its civilization crisis and the current pandemic is just its latest development. The 2008 crisis was a premonition of the crisis of the Capitalocene. The geologic era of the domination of Capital is coming to terms with Earth.
Keywords: Pandemia; Crisis; Capitalismo; Covid-19